Reform, revolution and crisis in Europe
1 online resource.
Keywords: "Today Europe stands at a crossroads unlike any it has faced since 1945. Since the 2008 financial crash, Europe has weathered the Greek debt crisis, the 2015 refugee crisis, and the identity crisis brought about by Brexit in 2016. The future of the European project is in doubt. How will Europe respond? Reform and revolution have been two forms of response to crisis that have shaped Europe's history. To understand Europe's present, we must understand that past. This interdisciplinary book considers, through the prism of several landmark moments, how the dynamics of reformation and revolution, and the crises they either addressed or created, have shaped European history, memory, and thought"--